Măsurarea performanțelor în administrație publică - Sorin Dan ȘANDOR; Horea RABOCA (Revista Transilvană de Ştiinţe Administrative, 2004)
Measuring performance is a more and more discussed topic in public administration. The key terms are: performance measurement, measure, measurement system. Performance measurement can be done at three different levels: individual, organizational and in a broader organizational context. Many models of performance measurement systems were proposed. The most influential one is the Balanced Scorecard Model (BSC), on which a possible application in the case of a university is presented.